Tindak Pidana Kesusilaan Di Media Sosial - Agustina, Agustina; Purnomo, Sagita (Legal Spirit, 2024)
This study aims to examine the elements of criminal acts of decency on social media, as well as comprehensively discuss policies and law enforcement against perpetrators of criminal acts of decency. This type of research is normative juridical with a descriptive-analytical approach discussing existing legal symptoms and problems, and testing them aware of laws and legal norms. The results of this study show that the elements of criminal acts of decency on social media as regulated by Article 281 of the Criminal Code are: whoever, intentionally, in public, distributes, distributes or transmits content that violates decency refers to the object of action in the Pornography Law. Policies and law enforcement against perpetrators of criminal acts of decency include penal policies regulated in Law Number 19 of 2016 concerning Electronic Information and Transactions, Law Number: 44 of 2008 concerning Pornography, and criminal acts of decency regulated by the Criminal Code. Non-penalty policy: supervision of sites or content on social media that contain moral content, understanding religious values from an early age, increasing healthy internet understanding, and parental supervision of minors in using social media/internet